Education in Biomedical and Health Informatics: A Mapping Approach - Kolokathi, Aikaterini; Mantas, John (Studies in health technology and informatics, 2018)
The emergence of the information technologies has seriously changed the healthcare system. Thus, health professionals need to be well-educated in order to respond successfully to the challenges of their job. In higher education programs in, biomedical informatics and health informatics are continuously developing. At this study more than 500 universities and colleges in Europe were checked in order to find related educational programs at all academic levels. The outcome of the research includes 316 study programs at undergraduate and postgraduate level including a variety of specializations. The majority of these programs are taking place in Czech Republic, Ireland and Austria. In contrast, countries such as Croatia and Cyprus have very low number of study programs in these fields.
Keywords: Curriculum; EFMI; Ireland; Health professionals; Czech Republic; Medical Informatics; health informatics; Chorvatsko; Kypr; Cyprus; kurikulum; Croatia; educational programs; lékařská informatika; Rakousko; Česká republika; Irsko; Austria